Clinical and microbiological characterization of patients with pneumonia associated with mechanical ventilation, Cienfuegos 2015-2017 - Roberto Carlos Barletta Farías; Leonardo Javier Pérez Ponce; Jorge Emilio Barletta del Castillo; Marcos Antonio González Guirola; Rolando Laín Sánchez Castellanos; Misael Pujol Pérez (Medisur)
Foundation: Pneumonia associated with mechanical ventilation is associated with high morbidity and mortality, and its integral management is complex. Objective: to describe the clinical and microbiological characteristics in patients with pneumonia associated with mechanical ventilation. Methods: an observational, descriptive, cross-sectional study was conducted. A total of 174 patients diagnosed with pneumonia associated with mechanical ventilation were analyzed in the period between January 2015 and December 2017, at the Provincial Hospital of Cienfuegos. The variables were considered: age, sex, service of origin, year and cause of admission, state at discharge, result of bacteriological culture, isolated microorganisms and resistance in vitro. Results: 26.4% of the patients were between 70-79 years old, with a predominance of males (52.3%). Monomicrobial cultures were present in 71.3% of the samples. The most frequent microorganism was Acinetobacter baumannii, with 50.5%. Cerebrovascular disease was the most frequent cause of admission (28.7%). 47.7% of patients died. There was a high resistance in vitro in most of the isolated microorganisms. Conclusion: the disease appeared mainly in elderly male patients. In correspondence with previous studies in the province, Acinetobacter baumannii was manifested as the most frequent causative agent, with high resistance in vitro. Cerebrovascular disease was the main cause of admission.